Unusual association of two rare entities: Primary rectal linitis and Klippel-Trenaunay syndrome - Haraki I; El Yazal S; Ait Errami A; Lairani FZ; Jiddi S; Samlani Z; Krati K; Oubaha S (Archives of Clinical Gastroenterology - Peertechz Publications, 2019)
Klippel-Trenaunay syndrome (KTS) is a rare congenital disorder, characterized by the triad of vascular malformations (angioma), venous and or lymphatic malformations and asymmetrical disturbed growth of soft tissues and/or bone. Primary rectal linitis is a rare digestive tumor with very poor prognosis. We report the case of a 41-year-old patient with Klippel trenaunay syndrome who was diagnosed with primary rectal linitis.